Mathematical methods in systems biology - Eugene Kashdan; Dominique Duncan; Andrew Parnell; Heinz Schättler (Mathematical Biosciences and Engineering)
The editors of this Special Issue of Mathematical Biosciences andEngineering were the organizers for the Third InternationalWorkshop "Mathematical Methods inSystem Biology" that took place on June 15-18, 2015 at the University College Dublin in Ireland. As stated in the workshop goals, we managed to attract a good mix of mathematicians and statisticians working on biological and medical applications with biologists and clinicians interested in presentingtheir challenging problems and looking to find mathematical and statistical tools for their solutions.For more information please click the “Full Text” above.